Mutant generation by allelic exchange and genome resequencing of the biobutanol organism Clostridium acetobutylicum ATCC 824. Issue 1 (December 2016) - Ehsaan, Muhammad; Kuit, Wouter; Zhang, Ying; Cartman, Stephen; Heap, John; Winzer, Klaus; Minton, Nigel
Abstract Background Clostridium acetobutylicum represents a paradigm chassis for the industrial production of the biofuel biobutanol and a focus for metabolic engineering. We have previously developed procedures for the creation of in-frame, marker-less deletion mutants in the pathogenClostridium difficile based on the use ofpyrE andcodA genes as counter selection markers. In the current study we sought to test their suitability for use inC. acetobutylicum. Results Both systems readily allowed the isolation of in-frame deletions of theC. acetobutylicum ATCC 824spo0A and thecac824I genes, leading to a sporulation minus phenotype and improved transformation, respectively. ThepyrE -based system was additionally used to inactivate a putative glycogen synthase (CA_C2239, glgA ) and the pSOL1 amylase gene (CA_P0168, amyP ), leading to lack of production of granulose and amylase, respectively. Their isolation provided the opportunity to make use of one of the keypyrE system advantages, the ability to rapidly complement mutations at appropriate gene dosages in the genome. In both cases, their phenotypes were restored in terms of production of granulose (glgA ) and amylase (amyP ). Genome re-sequencing of the ATCC 824 COSMIC consortium laboratory strain used revealed the presence of 177 SNVs and 49 Indels, including a 4916-bp deletion in the pSOL1 megaplasmid. A total of 175 SNVs and 48 Indels were subsequently shown to be present in an 824 strain re-acquired (Nov 2011) from the ATCC and are, therefore, most likely errors in the published genome sequence, NC_003030 (chromosome) and NC_001988 (pSOL1). Conclusions ThecodA orpyrE counter selection markers appear equally effective in isolating deletion mutants, but there is considerable merit in using apyrE mutant as the host as, through the use of ACE (Allele-Coupled Exchange) vectors, mutants created (by whatever means) can be rapidly complemented concomitant with restoration of thepyrE allele. This avoids the phenotypic effects frequently observed with high copy number plasmids and dispenses with the need to add antibiotic to ensure plasmid retention. Our study also revealed a surprising number of errors in the ATCC 824 genome sequence, while at the same time emphasising the need to re-sequence commonly used laboratory strains.